Ecologia da interação entre Cerconota Achatina (Zeller) (Lepidoptera: Oecophoridae) um engenheiro de ecossistema e sua planta, Byrsonima intermedia (a. Juss) (malpighiaceae) em vegetação de Cerrado - Borges, Mariana Velasque (2013)
When they are consumed on by herbivores, plants have a likely reduction in on fitness. Therefore there are several forms of plant defense antiherbivory. The principal forms are: the production of chemical and physical defenses, escape in time and space, tolerance to herbivory and indirect defense (which leads to attracting natural enemies to the plant). The escape in time, or phenological defense, comprises the features related to the rate of growth of parts to be consumed by herbivores. Studies of cyclical biological phenomena in a plant are called phenology. Similarly, the herbivores have developed features that allow for a better usage of host plants, the construction of leaf shelters is one of the most common forms of manipulation of the host. These changes alter the micro-habitat, modifying the biotic and abiotic conditions and thus changing the community associated with host plants, increasing the survival of its occupants. This modification is characterized as environmental engineering ecosystems and a feature has a bigger effect in seasonal environments such as the Cerrado. This study was conducted at Reserva Ecológica do Caça e Pesca do Itororó de Uberlândia, in the city of Uberlândia, MG between the years 2008-2011. The aim of this study was to investigate the interaction of the caterpillar Cerconota achatina, builder of leaf shelters on Byrsonima intermedia and its aggregation pattern, climate variability and plant phenology. We relate the phenological patterns of the plant with climatic variations and patterns of aggregation. We also observed the importance of the caterpillar as ecosystem engineer. We used 60 individuals of Byrsonima intermedia and monitoring conducted fortnightly, we quantified the number of leaves (mature and new), inflorescences, infructescences, herbivores and leaf shelters. In order to observe the effect of engineering, we quantify the amelioration of biotic and abiotic events. We quantify the effects of biotic factors measuring the survival of the caterpillar when exposed outside the shelter, and the abiotic factors comparing the difference in the temperature between the internal (inside the shelter) and external environment. In order to evaluate the effect of ecosystem engineering in the community, we provide artificial shelters in B. intermedia to be colonized. The plant presents low seasonality in the production of their vegetative organs (new leaves) and median seasonality of their reproductive aspects (inflorescences and fruits). The dominant herbivore (Cerconota achatina) had a strong tendency to seasonality. There was a high variation in the production of new leaves, inflorescences and fruits, during the three sampled years probably caused by a large variation in rainfall. The leaf shelters are present in almost all year at the plant, which could increase the survival of its producer (defense against predators and parasitoids and against climatic variations) and they are associated with increasing of the nutritional quality of plants. The leaf shelters caused a amelioration of the biotic (predation and parasitims) and abiotic (temperature) animals that occupy them, as well significantly increase the diversity and abundance of animals associated with B. intermedia. They are present all year, even in the dry season, the leaf shelters constructed by C. achatina cause a profound influence at the Cerrado, providing support for various species during the dry season and increasing the abundance and diversity of arthropods in the region.